2017
DOI: 10.1017/jfm.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-layer development and gravity waves in conventionally neutral wind farms

Abstract: While neutral atmospheric boundary layers are rare over land, they occur frequently over sea. In these cases they are almost always of the conventionally neutral type, in which the neutral boundary layer is capped by a strong inversion layer and a stably stratified atmosphere aloft. In the current study, we use large-eddy simulations (LES) to investigate the interaction between a large wind farm that has a fetch of 15 km and a conventionally neutral boundary layer (CNBL) in typical offshore conditions. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
219
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 120 publications
(245 citation statements)
references
References 95 publications
(134 reference statements)
24
219
2
Order By: Relevance
“…Several other studies also found enhanced gravity-wave activity during nighttime when the surface heat flux was negative (Brinkmann 1974;Whiteman and Whiteman 1974;Doyle et al 2005;Valkonen et al 2010). In large wind farms, gravity waves impose significant pressure gradients in the boundary layer and play an important role in redistributing energy throughout the farm (Allaerts and Meyers 2017). The objective of the current study is to investigate the impact of stable stratification on wind-farm performance and boundary-layer flow, with a particular interest in gravity waves.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Several other studies also found enhanced gravity-wave activity during nighttime when the surface heat flux was negative (Brinkmann 1974;Whiteman and Whiteman 1974;Doyle et al 2005;Valkonen et al 2010). In large wind farms, gravity waves impose significant pressure gradients in the boundary layer and play an important role in redistributing energy throughout the farm (Allaerts and Meyers 2017). The objective of the current study is to investigate the impact of stable stratification on wind-farm performance and boundary-layer flow, with a particular interest in gravity waves.…”
Section: Introductionmentioning
confidence: 84%
“…The subgrid-scale motions are modelled with the turbulent kinetic energy (TKE) model developed by Deardorff (1980), and classic Monin-Obukhov similarity theory is used to specify the boundary conditions near the surface. Following Allaerts and Meyers (2017), wind-farm entrance effects and boundary-layer development are included by using the concurrent-precursor method (Stevens et al 2014;Munters et al 2016), extended to include the effects of thermal stratification and Coriolis forces. Details of the LES methodology can be found in Appendix 1.…”
Section: Numerical Aspectsmentioning
confidence: 99%
See 3 more Smart Citations